Knowledge and attitude of nurses regarding mental illness - Gurung, G (Journal of Chitwan Medical College, 2014)
Although recent advances in psychiatry have increased our understanding towards psychiatric disorders, many people are unaware about mental illness and its treatment. The negative attitude is known hindrance of providing quality service to mental ill people. The aim of this study is to assess the knowledge and attitude about mental illness among nurses. The study was carried out in chitwan medical college, Bharatpur, Nepal. One hundred nurses working in different departments were the study population. A structured questionnaire was provided to the nurses for their responses. It was a purposive, descriptive study with 100 respondents of more than 2 years clinical experience. Almost all (99%) respondents mentioned that not all mentally ill are mad. Majority mentioned biochemical disturbances (99%) and genetic (51%) as cause of mental illness respectively. Respondents expressed their faith in psychiatrist (86%) in faith healers. This study revealed that there was overall adequate knowledge and positive attitude towards mentally ill people among the nurses. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10863 Journal of Chitwan Medical College 2014; 4(2): 40-43